Current Models of Investor State Dispute Settlement Are Bad for Health: The European Union Could Offer an Alternative; Comment on "The Trans-Pacific Partnership: Is It Everything We Feared for Health?" - Martin McKee; David Stuckler (Kerman University of Medical Sciences, 2017)
In this commentary, we endorse concerns about the health impact of the trans-pacific partnership (TPP), paying particular attention to its mechanisms for investor state dispute settlement. We then describe the different, judgeled approach being advocated by the European Commission team negotiating the Trans-Atlantic Trade and Investment Partnership, arguing that, while not perfect, it offers significant advantages.